Tongues on fire Caribbean lesbian lives and stories - Elwin, Rosamund (Women's Press, 2008)
In Tongues on Fire, Caribbean lesbians speak zami desire honestly and eloquently, loudly and clearly. Narrating their life stories, they claim what has never been acknowledged―lesbian history and continuity in the Caribbean. They collectively honour that history and continuity in fiction sweet with intimacy, sensuality, and memory. Like the lives and stories of Caribbean lesbians, Tongues on Fire is unique. Rosamund Elwin has put together a fine collection that includes well-known writers such as Michelle Cliff, Shani Mootoo, and Makeda Silvera.
Keywords: amériques; arts; caraïbes; discipline; histoire et politique; personnes lesbiennes; ressource en ligne; roman; régions géographiques; sexualité; thématiques; émotions; études littéraires

Getting wet: Tales of lesbian seductions - Allain, Carol; Elwin, Rosamund (Women's Press, 1992)
This is sex fiction that gets under the covers and rolls them back, sex fiction that inscribes lesbian erotics poignantly, playfully and powerfully.
Keywords: 1900-1999; amériques; approches et analyses; canada; corps; lesbianisme; périodes historiques; ressource en ligne; régions géographiques; sexualité; thématiques; érotisme